Understanding the Aspect of Legal Certainty in the Binding Agreement for the Sale and Purchase of Shares - gultom, elisatris; Reza Liasta Dewi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
A share sale and purchase agreement (PPJB) is commonly used as a preliminary agreement before the transfer of rights becomes valid. However, its validity and binding force are still debated, especially when the transfer of rights to shares is included in a dispute in court. This paper aims to answer the problem of the position of PPJB from the perspective of agreement law and the legal certainty aspects of PPJB shares as part of the legal protection of the parties. The research method used is normative juridical by examining secondary data sourced from primary, secondary and tertiary legal materials, especially those correlated with the research topic. The description-analytical method is used to describe the existence of PPJB in the process of transferring shares to be further analyzed using legal principles and concepts so that its validity and binding force can be known. The results show that from the perspective of agreement law, the position of the PPJB is valid and has binding force for the parties if the material and formal requirements of the PPJB have been fulfilled. The transfer of shares is juridically transferred after the PPJB is followed by the fulfillment of the requirements stipulated in the PPJB and followed up with the notarial deed of transfer of shares and the recording of the transfer of shares in the company's register of shareholders.